2022
DOI: 10.3390/agronomy12020455
|View full text |Cite
|
Sign up to set email alerts
|

Wax Extracted from Waste Cauliflower Leaves Shows Potential Antitranspirant Efficacy When Applied to Rapeseed Plants

Abstract: The stress from excessive transpiration of water from plant leaves can damage crop growth during droughts. Specific commercial biostimulant products (antitranspirants) are available to reduce transpiration when applied to plants, but these products are expensive. Antitranspirants from waste would be cheaper, and the aim of this research was to extract leaf wax from a fresh produce processing waste and conduct a preliminary evaluation of its antitranspirant efficacy. Supercritical CO2 was used to extract wax fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Granger and Trager, 2002) has been done on them. Faralli et al (2022) who evaluated wax extracted from cauliflower waste on rapeseed found the product as effective as di-1-p-menthene in reducing stomatal conductance and improving water use efficiency. In bedding plants, a low concentration (10 mM) of food-grade vinegar (acetic acid) improved plant survival following 3–4 weeks of drought (Allen and Allen, 2021).…”
Section: Commercial Uses Of Antitranspirants In Horticulturementioning
confidence: 99%
See 1 more Smart Citation
“…Granger and Trager, 2002) has been done on them. Faralli et al (2022) who evaluated wax extracted from cauliflower waste on rapeseed found the product as effective as di-1-p-menthene in reducing stomatal conductance and improving water use efficiency. In bedding plants, a low concentration (10 mM) of food-grade vinegar (acetic acid) improved plant survival following 3–4 weeks of drought (Allen and Allen, 2021).…”
Section: Commercial Uses Of Antitranspirants In Horticulturementioning
confidence: 99%
“…Therefore, relatively speaking, for arable crop production, the current commercial ATs are expensive, as Faralli et al (2022) noted. Another reason for the neglect of ATs in crop production could be the erroneous conclusion of AT research in the 1970s that discouraged the use of ATs in crop production.…”
Section: In Arable Crop Productionmentioning
confidence: 99%
“…For example, one of the common commercial products, di‐1‐ p ‐menthene, is derived from pine resin 8 . Other polymers which can act as stomatal blockers and are possibly even more‐acceptable to consumers are natural products derived from plant extracts without chemical modification and may include extracted leaf wax, 16 and vegetable oil 17 . An additional advantage of vegetable oils is their much lower cost, and as a consequence they may be more likely to be adopted by smallholder farmers in low‐income countries.…”
Section: Stomatal Blockersmentioning
confidence: 99%